Market Penetration Strategies and Competitive Advantage of the Telecommunication Firms in Kenya - Gitonga, George; Kariuki, Paul; Kimani, Ezekiah (International Journal of Strategic Management, 2025)
Purpose: The primary purpose of this study was to investigate the effects of market penetration strategies on the competitive advantage of telecommunication firms in Kenya. Specifically, the study sought to establish the influence of market penetration strategies on competitive advantage and to examine the moderating effect of ICT regulatory policy on the relationship between market penetration strategies and competitive advantage. The research was driven by critical challenges in the Kenyan telecommunication sector, including declining voice revenues, regulatory shifts, technological disruptions, and evolving customer demands. Methodology: A total of 130 respondents, drawn from a pool of 196 senior and middle-level managers across five telecommunication firms in Kenya, participated in the study. The respondents were selected using purposive sampling to ensure targeted representation. Data were collected using structured questionnaires and analyzed using descriptive and inferential statistical techniques. Findings: Regression analysis revealed a strong positive relationship (R = 0.781) between market penetration strategies and competitive advantage, indicating that these strategies are fundamentally linked to firm performance. The R-squared value of 0.610 demonstrated that 61.0% of the variation in competitive advantage could be attributed to changes in market penetration strategies. Furthermore, the analysis confirmed that ICT regulatory policy significantly moderates this relationship, highlighting its critical role in shaping competitive dynamics within the industry. The study concludes that a robust causal relationship exists between market penetration strategies and competitive advantage. Effective implementation of these strategies significantly enhances competitive positioning. Additionally, ICT regulatory policies play an integral role in moderating this relationship, emphasizing their importance in influencing market behaviors and the success of market penetration efforts. Unique Contribution to Theory, Practice and Policy: The study was grounded in three theoretical frameworks: Ansoff Matrix Theory, Competitive Advantage Theory and Regulatory Capture Theory, which provided a foundation for understanding the strategic and regulatory dimensions of market penetration and competitive advantage.Based on these findings, the study recommends that ICT regulatory policies be structured to support informed decision-making and promote growth and operational efficiency within the telecommunications sector. Policymakers are encouraged to align regulations with competitive strategies to foster synergy, sustain market penetration efforts, and strengthen competitive advantage. For academia and industry, the study serves as a valuable resource for future research and a practical guide for managers seeking to optimize business operations and implement effective growth strategies to enhance competitive performance.